2010
DOI: 10.1097/cmr.0b013e32833906e3
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase mRNA levels in the blood of uveal melanoma patients: correlation with the number of circulating tumor cells and tumor progression

Abstract: We measured tyrosinase mRNA levels by real-time quantitative reverse transcription-PCR (qRT-PCR), in the blood of patients with uveal melanoma. Results were correlated with clinical data and, in a subgroup of patients, with the number of circulating tumor cells (CTC) assessed using isolation by size of epithelial tumor cells (ISET). Forty-one patients with uveal melanoma were longitudinally investigated over a period of 5 years. The standard curve of the qRT-PCR method used melanoma cell line SK-MEL-28, added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
1
42
0
1
Order By: Relevance
“…Serum tyrosinase m-RNA levels have been shown to be increased in patients with primary uveal melanoma, and they correlate with metastatic disease. In addition, tyrosinase m-RNA can be used for the indirect quantification of circulating tumour cells and have been correlared with the dimensions of the primary tumour [61]. …”
Section: Metastasesmentioning
confidence: 99%
“…Serum tyrosinase m-RNA levels have been shown to be increased in patients with primary uveal melanoma, and they correlate with metastatic disease. In addition, tyrosinase m-RNA can be used for the indirect quantification of circulating tumour cells and have been correlared with the dimensions of the primary tumour [61]. …”
Section: Metastasesmentioning
confidence: 99%
“…In a previous paper [8] we studied a group of 41 patients affected by uveal melanoma including small, medium and large size tumors (Collaborative Ocular Melanoma [9]) followed for a period of up to 55 months. The study was performed by RT-qPCR for the measurement of tyrosinase mRNA in blood as a means to detect and indirectly quantify the number of CTC.…”
Section: Introductionmentioning
confidence: 99%
“…Bluemke et al (15) and McKiernan et al (35) also reported that there was no correlation between the presence of CTCs and tumor size in RCC. However, Pinzani et al (36) demonstrated that the messenger RNA levels of tyrosinase, which can be taken as an indirect parameter correlated to the number of CTCs, were significantly correlated with tumor dimension and disease-free and overall survival through reverse transcription-quantitative polymerase chain reaction analysis of blood from 41 patients with uveal melanoma. In the present study, there was no correlation between the positive staining rate and age, gender, tumor size, the pathological pattern, T classification, Fuhrman grade, presence of a lesion or metastasis to the lungs in 27 metastatic patients.…”
Section: Discussionmentioning
confidence: 99%